Morphological and Proliferative Responses of Rat Microglia Cells to Lipopolysaccharide and Β-Amyloid - Badiei, Alireza (2008)

(untitled)
Microglia are the residential macrophages of the central nervous system (CNS) and are sensitive to any changes in their environment. There is rapid microglial activation in most pathological conditions in CNS. The association of activated microglia with various inflammatory and neurodegenerative diseases are well documented. In this study we evaluated the in vitro responses of microglia to lipopolysaccharide (LPS) or beta amyloid (Aβ) in an attempt to further define the activation of microglia. LPS is a potent activator of monocytes and macrophages and Aβ is used to activate microglia in vitro into a neurotoxic phenotype distinguished by secretion of proinflammatory molecules. Microglia were cultured from Sprague-Dawley neonatal rats and purity of culture determined using a common marker for microglia, lectin. Morphological changes following LPS or Aβ treatment were evaluated using fluorescent and confocal microscope. Treated microglia assumed a deramified shape with a condensed cytoplasm, typical of activated microglia. Stimulation of microglia with LPS or Aβ also resulted in significant ultrastructural changes. Transmission electron microscopy revealed an increased number of enlarged, elongated and swollen mitochondria. There were also some changes in the appearance of the endoplasmic reticulum. Untreated microglia displayed mainly smooth endoplasmic reticulum (SER) whereas LPS-treated cells displayed polyribosomes and rough endoplasmic reticulum (RER). It is therefore assumed that LPS-treated microglia have an increased ability in synthesising protein, some of which may be secretory molecules necessary for inflammation. Aβ-treated microglia also displayed more RER compared to control, but lesser compared to LPS. The nucleus in treated microglia appeared enlarged in comparison to untreated cells. The number of cells following treatment revealed that microglia are more viable following LPS treatment compared to Aβ. Immunophenotyping assays demonstrated upregulation of MHC II and CD40 by microglia following treatment. Both MHC II and CD40 are implicated in antigen-presenting and this result indicates that in comparison to LPS, Aβ may have more ability to induce antigen-presenting capabilities in microglia. As shown by viability counts, carboxy fluorescein succinimidyl ester (CFSE) staining also revealed no microglia proliferation following treatment with LPS and Aβ. In conclusion, our study illustrates activation-induced alterations in the morphology, ultrastructure and cell surface phenotype of microglia, which were not accompanied by proliferation of microglia. These changes represent the range of effects that occur in microglia following activation. In an attempt to culture microglia from adult rats for the purpose of determining the effects of aging on microglia responses, modifications were made on the established protocol for neonatal microglia cultures. This includes growing adult cells on poly-L-lysine-coated tissue culture flasks and substituting insulin in cell culture media with insulin-transferrin-selenium (ITS). We were able to successfully support the in vitro growth of adult microglia, which was also enhanced with the addition of the growth factor M-CSF. Key words: microglia, lipopolysacharide, beta amyloid, morphology, proliferation, CD40/MHC II